Health related quality of life, service utilization and costs for patients with Huntington's disease in Norway - Marleen R. van Walsem; Jan C. Frich; Monica Gómez Castañeda; Emilie Isager Howe; Lasse Pihlstrøm; Nada Andelic; Eline Aas (BMC, 2022)
Abstract Background Huntington's disease (HD) is a progressive genetic neurodegenerative disease accompanied by mental and neurocognitive disabilities, which requires long-term and comprehensive treatment and care. Information on the health and economic burden of HD is scarce, but essential for conducting health economic analyses, in light of the prospect of new therapies for HD. In this study, we aim to identify values for Health-Related Quality of Life (HRQoL), describe service utilization and costs, and their associations with clinical and socio-demographic variables across all phases of HD. Methods A cross-sectional study including 86 patients across all phases of HD. Values of HRQoL were calculated based on EQ-5D-3L index scores. Additionally, health care and societal costs were estimated based on service utilization collected using the Client Service Receipt Inventory (CSRI) and data from the patients' interviews. Total societal costs included costs of primary and secondary health care services, informal care and productivity loss of the patients. Multiple regression analyses were used to investigate associations between socio-demographic and clinical variables on HRQoL and costs. Results HRQoL values declined, while total costs increased across disease severity. Total six-month healthcare costs and total societal costs were € 18,538 and € 66,789 respectively. Healthcare and societal costs doubled from early to middle phase, and tripled from middle to advanced disease phase. Main six-month cost components for the three disease phases were informal care costs (€ 30,605) accounting for approximately half the total societal costs, and costs due to production loss (€ 18,907) being slightly higher than the total healthcare costs. Disease severity and gender were found to have the strongest effect on both values of HRQoL and costs. Conclusions Reported values of HRQoL and costs including costs for production loss may be used in modelling the cost-effectiveness of treatment for HD. Our results highlight the crucial role the informal caregivers play in the care provided to HD patients in all disease phases. Future research should focus on the estimation of productivity loss among informal caregivers.